2012
DOI: 10.1007/bf03391821
|View full text |Cite
|
Sign up to set email alerts
|

Description of a Practitioner Training Program on Functional Analysis and Treatment Development

Abstract: The current project examined the effectiveness of a functional analysis skills training package for practitioners with advanced degrees working within an applied setting. Skills included appropriately carrying out the functional analysis conditions as outlined by Iwata, Dorsey, Slifer, Bauman, and Richman (1982/1994), interpreting multielement functional analysis graphs using the methodology described by Hagopian et al. (1997), determining next steps when functional analysis data are undifferentiated, and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…The results showed that performance improved from baseline and maintained for 19 of 20 participants following experience with the computer‐based training. This study extends the work of Chok et al () by demonstrating the efficacy of a stand‐alone, computer‐based tutorial that was administered from start to finish within a 1‐day period to a large number of trainees concurrently without the presence of a staff trainer. These findings also replicate the research on training participants to identify relevant antecedent and consequences in conditions of a standard functional analysis (e.g., Iwata et al, ; Lambert, Bloom, Kunnavatana, Collins, & Clay, ; Moore et al, ; Phillips & Mudford, ; Wallace et al, ) and shows computer‐based training as an option for training participant skills.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The results showed that performance improved from baseline and maintained for 19 of 20 participants following experience with the computer‐based training. This study extends the work of Chok et al () by demonstrating the efficacy of a stand‐alone, computer‐based tutorial that was administered from start to finish within a 1‐day period to a large number of trainees concurrently without the presence of a staff trainer. These findings also replicate the research on training participants to identify relevant antecedent and consequences in conditions of a standard functional analysis (e.g., Iwata et al, ; Lambert, Bloom, Kunnavatana, Collins, & Clay, ; Moore et al, ; Phillips & Mudford, ; Wallace et al, ) and shows computer‐based training as an option for training participant skills.…”
Section: Discussionsupporting
confidence: 73%
“…Module 4 provided an overview of the decision making protocol (see Supporting Information). This module guided participants on whether to refer the client to treatment and what, if any, functional analysis variation should be implemented following undifferentiated data paths (Chok et al, ; Vollmer et al, ). For example, if the maintaining variables of the target behavior could not be identified when presented with a brief functional analysis graph (Northup et al, ), the module suggested transitioning to a multielement functional analysis (Iwata et al, /94).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Steve had a long history of engaging in aggression during transitions but limited assessment had been performed to identify the evocative and maintaining influences. A functional analysis such as the one conducted in this study is well suited to the demands of most applied settings, can quickly reveal differential responding between test-control conditions, and represents a methodology that can be taught to and implemented by care-providers (Chok, Shlesinger, Studer, & Bird, 2012). Of course, these analyses can reveal more than one hypothesized function.…”
Section: Treatment Implications Of the Casementioning
confidence: 99%